THE IMPLEMENTATION OF AR RAHN CONTRACTS - Iryanti, Andina Dwi (UG Journal, 2021)
The Islamic finance industry has developed quite rapidly and has been accepted by the Indonesian people. Many products appear, such as Banking Funding and Financing, Leasing, Insurance and Pawn. Indonesian people, especially the lower middle class, as Indonesia a developing country, are familiar with pawn products. I n 2010 the Central Bank of Indonesia adopted a policy that Pawn can no longer be a monopoly which caused a spurt of Ar Rahn in Islamic Banks product. This phenomenon shows that the public's interest of Ar Rahn's is great so the availability of many branches are to serve public. This research also aims to complete the Islamic Finance study, because so many arthicles about Banking, Leasing, and Insurrance but rare about Rahn. This research using descriptive qualitative method, with internship for a month on headquarters of PT. Pegadaian (Persero), focusing on syariah division and syariah operational main branch to understand the theoretical comes with practice. At the end, we can find out that Rahn customers are no longer the poor but also the rich who believe there is also an investment on gold through pawning. In general, The Rahn aqad can be grouped into two, consumption and production. The consumption objective of Rahn is for medical expenses, education expenses, etc. Whereas for the productivepurposes, Rahn can be done through 3 (three) schemes/aqad namely Mudharaba, Murabaha and Musharaka contract.